Gladiolus Growth and Flowering: Impact of Chemicals And Plant Growth Regulators (Annals of Bangladesh Agriculture, 2022)
To study the growth and flowering of gladiolus by using different chemicals and PGR, an experiment was conducted at the research field of the Department of Horticulture, Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur from September 2019 to May 2020. Medium sized (3.5-4.5 cm) corms of the variety BARI gladiolus-3 were planted at about 6-9 cm depth in a unit plot of 1.8 m X 1.2 m maintaining a spacing of 30 cm X 20 cm following Randomized Complete Block Design (RCBD) with 3 replications. Foliar spray with 3 levels of GA3 (150, 200 and 250 ppm), 2 levels of KNO3 (1 and 2%) and 2 levels of Ca(NO3)2 (1 and 2%) along with control (only tap water) was done at 30, 45 and 60 days after planting (DAP). Results revealed that although, the tallest plant (62.9 cm) was observed in T3; where, GA3 was applied at the highest concentration (250 ppm) but it was statistically at par with the height recorded in T2 (60.7 cm) and T4 (59.4 cm); where, GA3 was applied @ 200 ppm and KNO3 was applied @ 1%, respectively. Although, Spike length in T3 (85.7 cm) varied statistically with T2 (75.9 cm) but rachis length in T3 (57.4 cm) was statistically similar with T2 (56.8 cm). Floret length and breadth in T2 (11.3 cm and 11.3 cm, respectively) were higher than T3 (10.7 cm and 10.8 cm, respectively). Number of floret per spike was statistically similar in all treatments except T4 (12.7) and T7 (12.4). The highest leaf area was recorded in T5 (189.5 cm2); where, KNO3 was applied @ 2% and this was statistically similar to all other treatments except T6 (148.9 cm2); where Ca(NO3)2 was applied @ 1%. On overall consideration, gibberellic acid (GA3) @ 250 ppm may be used for better growth and flowering of gladiolus.Ann. Bangladesh Agric. (2021) 25 (1) : 67-78